Morphometric Analysis for Drainage Network of Yarmouk Basin in Jordan: A Study in Applied Geomorphology via Geographic Information System (GIS) - Zairer, Osama Abdullah (Journal of Humanities & Social Sciences, 2024)
This study were carried out in order to analayze and interpretation the morphometric parameters Characteristics of the drainage network of the Yarmouk Basin in Jordan via Geographic Information System (ARCGIS9) and the digital elevation model (DEM), also standard mathematical models, the study area lies in northwestern part of Jordan, covers an area of approximately 1410 km2 and, dominated by arid and semi arid climate where geological formations spreaded belonging to the Upper Cretaceou. The results of the morphometric parameters analysis has shown the basin pear-shaped formed where factor ratio (0.32) Circularity and Elongation ratio is (0.30) and (0.61) respectively.The basin relief morphometric parameters also shown relief ratio (20.6m/km) and the hypsometric coefficient (56%) this indicates varying stage that of both equilibrium mature stage and in-equilibrium young of the basin.the Drainage density reached 1.1 km / km2, its low densities and river frequency 0.58/km2 also bifurcation ratio 3.4 which is influenced by climate, vegetation cover, rokss type, the yarmouk river basin has 6th order (stream order) and the drainage network pattern is dendritic.